Pemanfaatan Sampah Plastik Sebagai Bahan Pembuat Roster - Daud Adi Riyono; Maria Roosa Srah Darmanijati; Irene Arum AS (Environmental Insight Journal, 2026)
Plastic waste has become a growing environmental concern due to its resistance to natural degradation. Plastics possess several advantageous properties, including water resistance, corrosion resistance, low weight, and high flexibility. Polyethylene Terephthalate (PET) and Low-Density Polyethylene (LDPE) are commonly found in waste. This research aims to process these plastics into roster (ventilation blocks) as an alternative material for non-structural construction. The plastic was melted and then molded using a 5 cm  5 cm  5 cm mold to create test samples for compressive strength and water absorption testing. Products of the rosters were tested for light and wind penetration. The study showed that the average compressive strength of the PET roster was 4.10 N/mm², LDPE roster did not exhibit a distinct collapse point but demonstrated a superior capacity to withstand loads. The water absorption values for the PET and LDPE rosters were 0.15% and 0.67%, respectively. Both types satisfied the water absorption requirements of the Indonesian National Standard. Furthermore, light and wind penetration testing revealed no significant differences between the PET and LDPE blocks. Based on these findings, ventilation blocks fabricated from plastic waste are considered highly feasible and possess strong potential as an alternative, eco-friendly non-structural construction material.